PENGARUH MODAL DAN TENAGA KERJA PER JENIS INVESTASITERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN SLEMAN PASCA OTONOMI DAERAH, TAHUN 2001-2005 - Rudy Badrudin (Fakultas Bisnis UKDW, 2011)
This research analyze the effect of capital and labor of Foreign Investment, Local Investment, and Non-facility Investment on Gross Domestic Regional Product in Sleman Regency afterregional autonomy. Based on research method using 3 models of regression equation with significance level of 5%, the result are capital and labor of Foreign Investment had nosignificant effect on Gross Domestic Regional Product in Sleman Regency; capital of Local Investment had no significant effect on Gross Domestic Regional Product in Sleman Regencyand labor of Local Investment had significant effect on Gross Domestic Regional Product in Sleman Regency, capital and labor of Non-facility Investment had no significant effect onGross Domestic Regional Product in Sleman Regency.Keywords: capital, labor, foreign invesment, local invesment, non-facility invesment